Dirichlet Problem for Degenerate Quasilinear Elliptic Equations Suggested by the Anisotropic Permeation (Journal of Partial Differential Equations, 2020)
By Browder's pseudo-monotone operator theory and the techniques belonging to J. Leray and J. Lions, the existence theorem of the generalized solution of the Dirichlet problem for a strongly degenerate quasilincar elliptic equation has been proved in the anisotropic Sobolev space.
Keywords: Degenerate equation; imbedding theorem; anisotropic permeation; pseudo-monotone operator